2005
DOI: 10.1111/j.1469-7580.2005.00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the lactating human breast redefined with ultrasound imaging

Abstract: The aim of this study was to use ultrasound imaging to re-investigate the anatomy of the lactating breast. The breasts of 21 fully lactating women (1-6 months post partum) were scanned using an ACUSON XP10 (5-10 MHz linear array probe). The number of main ducts was measured, ductal morphology was determined, and the distribution of glandular and adipose tissue was recorded. Milk ducts appeared as hypoechoic tubular structures with echogenic walls that often contained echoes. Ducts were easily compressed and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
194
0
18

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(217 citation statements)
references
References 25 publications
5
194
0
18
Order By: Relevance
“…In Sir Astley Cooper studies 25 it was revealed that human breast tissue is organized into separate lobes, each composed of a ductal tree. Preliminary ultrasound studies of a lactating breast 37 were attempted, as well as detection of sectional ductal structures using second-order shape measurements 38 . However, no imaging method has succeeded thus far revealing the entire ductal systems in both breasts in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In Sir Astley Cooper studies 25 it was revealed that human breast tissue is organized into separate lobes, each composed of a ductal tree. Preliminary ultrasound studies of a lactating breast 37 were attempted, as well as detection of sectional ductal structures using second-order shape measurements 38 . However, no imaging method has succeeded thus far revealing the entire ductal systems in both breasts in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Although V m may be altered because of breast feeding, the alternation was presumed to be insignificant for the sake of simplification. This simplification was based on the consideration that the volume of milk provided for a single feeding is small (approximately 150 ml) compared with the total volume of milk accumulated in the breasts (approximately 500 ml on average) (Daly et al, 1993;Ramsay et al, 2005). Finally, the f p values used in the present study were obtained from the DrugBank database (http://www.…”
Section: Methodsmentioning
confidence: 99%
“…Between 4 and 18 main milk ducts exit at the nipple, and the ductal network is complex and heterogeneous and not always arranged symmetrically nor in a perfect radial pattern as anatomically illustrated. 4 The most commonly used imaging tool for the breast is digital mammography. On mammography imaging, fibroglandular tissue appears white, with darker gray surrounding and interposed fat (Fig.…”
Section: Normal Parenchymal Breast Anatomymentioning
confidence: 99%